Preparation method of asymmetric compact polymer pervaporation membrane

By using alkali treatment and metal ion crosslinking to etch and crosslink the PI membrane, the swelling problem of the pervaporation membrane during use is solved, and the permeability and selectivity are improved simultaneously. The process is simple and environmentally friendly.

CN121669003APending Publication Date: 2026-03-17XIAMEN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610080068.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-01-21
Publication Date
2026-03-17

AI Technical Summary

Technical Problem

Existing pervaporation membranes are prone to swelling during use. Traditional modification methods are difficult to improve permeability and selectivity simultaneously, and the processes are complex and not environmentally friendly. Metal crosslinking is mainly used for the modification of thin film composite membranes but has failed to improve the porous structure of the support layer and the crosslinking degree of the selective layer.

Method used

A combination of alkali treatment and metal ion crosslinking was used to etch and crosslink the support layer of a dense PI film. The microstructure and hydrophilicity/hydrophobicity of the film were controlled by adjusting the concentration and time of the alkali solution. The degree of crosslinking and pore structure were improved by metal ion replacement.

Benefits of technology

While maintaining a relatively constant permeation flux, the separation factor was significantly improved, achieving simultaneous enhancement of membrane morphology, hydrophilicity/hydrophobicity control, and anti-swelling performance. The process is simple and environmentally friendly.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121669003A_ABST
    Figure CN121669003A_ABST
Patent Text Reader

Abstract

A preparation method of an asymmetric dense polymer pervaporation membrane belongs to the field of separation membrane preparation, and comprises the following steps: 1) preparing an integrated symmetric dense polymer membrane, and contacting the lower side of the membrane with alkali liquor; and 2) cleaning the treated membrane with distilled water to remove residual alkali liquor. Freeze-drying the modified membrane; and 3) fixing the treated membrane in a plate frame, pouring a metal salt solution, soaking, washing to remove the residual salt solution on the surface of the membrane, and freeze-drying the prepared metal ion cross-linked membrane. According to the invention, the synchronous completion of the construction of the loose support layer and the compact cross-linked selection layer is realized through the etching of the polymer film and the metal cross-linking in the film forming process by fully utilizing the etching of the polymer film material and the alkali liquor on the polymer film and the difference of interaction forces between different metal ions and the polymer material, so that the operation process is simplified, and the production efficiency is improved. The technical problems of flow complexity, environmental friendliness and performance tradeoff effect of a traditional etching modification or cross-linking modification method can be solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of separation membrane preparation, and more particularly to a method for preparing an asymmetric dense polymer pervaporation membrane, suitable for pervaporation dehydration. Background Technology

[0002] With increasing awareness of environmental protection and resource recycling, bioethanol is gradually gaining attention. As a multifunctional chemical, ethanol is widely used in various fields, including fuel production, food and beverage, pharmaceuticals and healthcare, and chemical manufacturing, and its application scope continues to expand. Pervaporation (PV), as an emerging membrane separation technology, shows great promise in separating biomass ethanol. Compared with traditional separation technologies, pervaporation not only has advantages such as small footprint, simplicity, and flexibility, but it can also significantly reduce energy and resource consumption during the separation process. The selection of membrane materials is crucial for pervaporation. Polyimide (PI), in addition to its excellent film-forming properties and heat resistance, also possesses balanced chemical and mechanical properties, making it one of the ideal pervaporation membrane materials. However, during use, due to prolonged contact between the feed liquid and the membrane module, the polyimide membrane inevitably swells, leading to a decline in its performance. Crosslinking modification can improve the swelling resistance of polyimide to some extent. However, traditional chemical crosslinking often struggles to overcome the trade-off between permeability and selectivity, involves complex molecular structure design, is not environmentally friendly, and requires cumbersome process parameter optimization. There is currently no simple modification method that can simultaneously optimize the morphology of PI membranes, control hydrophilicity / hydrophobicity, and improve swelling resistance. Metal ions, as crosslinking agents, are mainly used in organic solvent nanofiltration and gas separation, and have also been reported in pervaporation. However, their application is primarily in modifying the base membrane of thin-film composite membranes and enhancing the interaction between the base membrane and the selective layer. They have not been able to simultaneously improve the porous structure of the support layer and the crosslinking degree of the selective skin, nor have there been reports of combining metal crosslinking with alkali treatment modification to simultaneously improve the crosslinking degree and pore structure of the membrane. Summary of the Invention

[0003] The purpose of this invention is to solve the aforementioned problems in the prior art and provide a method for preparing an asymmetric dense polymer pervaporation membrane. This method uses a mild and simple alkali treatment followed by ion exchange to simultaneously improve the crosslinking degree, hydrophilicity, and pore structure of the pervaporation membrane. By simultaneously modifying the support layer side of the dense PI membrane with alkali etching and metal ion crosslinking, the alkali solution partially etches the lower side of the PI membrane, transforming it into an asymmetric PI membrane, and generating crosslinked sodium polyaminate on its surface. By changing different alkali concentrations and alkali treatment times, the microstructure and hydrophilicity / hydrophobicity of the PI membrane can be controlled, achieving a simultaneous increase in pervaporation flux and separation factor. Furthermore, by using metal ion replacement to enhance the complexation strength of the polyaminate, a significant increase in the separation factor is achieved without a substantial change in the permeation flux of the PI membrane. In summary, this invention combines simple alkali treatment and metal ion replacement to simultaneously improve the morphology optimization, hydrophilicity / hydrophobicity control, and anti-swelling ability of an integrated PI membrane, thereby overcoming the common trade-off effects in pervaporation membranes. This is a green and efficient method for preparing pervaporation membranes.

[0004] To achieve the above objectives, the present invention adopts the following technical solution:

[0005] A method for preparing an asymmetric dense polymer pervaporation membrane includes the following steps:

[0006] 1) Contact the underside of the integrated symmetrical dense polymer film with an alkaline solution for a period of time, then clean and dry it;

[0007] 2) The membrane treated in step 1) is brought into contact with a metal salt solution for ion exchange treatment, followed by cleaning and drying.

[0008] The alkaline solution is an aqueous solution of sodium hydroxide, potassium hydroxide, calcium hydroxide, or barium hydroxide, with a concentration of 0.1~10M; the time period is 0.5~12 h.

[0009] Preferably, the concentration of the alkaline solution is 0.1~2 M; and the time period is 0.5~10 h.

[0010] The metal ions in the metal salt solution are Ca. 2+ Ni 2+ Zn 2+ Mg 2+ Co 2+ Ag + Fe 2+ Al 3+ Cu 2+ or Fe 3+ The concentration of the metal salt solution is 0.01~1 M; the ion exchange treatment time is 1~24 h.

[0011] The integrated symmetrical dense polymer membrane is a polyimide membrane, a polyacrylonitrile membrane, or a polyvinylidene fluoride membrane.

[0012] An asymmetric dense polymer pervaporation membrane is prepared using the method described in this invention.

[0013] The cross-sectional morphology of the asymmetric dense polymer pervaporation membrane is asymmetric, comprising a dense layer and a support layer with a porous structure; and the gel content of the membrane in a strong organic solvent (such as N-methylpyrrolidone) is not less than 50 wt%.

[0014] The application of the asymmetric dense polymer pervaporation membrane described in this invention in the pervaporation separation process.

[0015] The pervaporation separation process is used to separate water from an aqueous solution of organic matter with a mass concentration of not less than 50%.

[0016] In this invention, the cleaning process involves rinsing with distilled water at least three times to remove residual alkali and residual metal salt solutions. The drying process is freeze-drying.

[0017] Compared with the prior art, the beneficial effects achieved by the technical solution of this invention are:

[0018] 1. A polymer film with strong complexation crosslinking can be obtained through alkali modification and subsequent metal ion replacement.

[0019] 2. After alkali treatment, the microstructure of the polymer membrane changes from a uniform and dense structure to a loose and porous structure on one side of the support layer. This not only simultaneously improves the membrane's porosity and hydrophilicity but also achieves ionic crosslinking of the polymer membrane. Thus, the membrane's microstructure, hydrophilicity / hydrophobicity, and degree of crosslinking are simultaneously optimized and modified.

[0020] 3. Changing the concentration and time of alkali treatment can optimize the effect of modification on the chemical structure, microstructure, physicochemical properties and pervaporation performance of polymer membranes, resulting in metal ion crosslinked polymer membranes with improved crosslinking degree and enhanced pervaporation performance. These membranes are suitable for the field of pervaporation dehydration and show broad application prospects in this field.

[0021] 4. The cross-linking strength of the polymer membrane is further improved by metal ion replacement. Compared with the polymer membrane modified only by alkali (sodium ion cross-linking membrane), the separation factor is significantly improved with little change in flux.

[0022] 5. The present invention has a simple process and is environmentally friendly. It uses a simple one-step alkali treatment modification and subsequent metal ion replacement to modify the polymer membrane, which solves the problem that traditional dense membrane modification cannot overcome the flux-separation factor trade-off effect, and achieves simultaneous improvement in membrane pore morphology, crosslinking degree and surface hydrophilicity. Attached Figure Description

[0023] Figure 1 This is a schematic diagram of the process for preparing the dense polymer film according to the present invention;

[0024] Figure 2 This is a schematic diagram of a pervaporation testing apparatus;

[0025] Figure 3 This is a schematic diagram illustrating the mechanism of metal ion crosslinking of polyimide (PI) films;

[0026] Figure 4 Infrared spectra (left) and XPS broad peak scans (right) of the original and modified PI films;

[0027] Figure 5 Infrared spectra of PI films at the original state and under different alkali treatment times;

[0028] Figure 6 The weight loss rate of PI membrane under different alkali treatment times;

[0029] Figure 7 The microstructure of the original PI membrane and the cross-section of the PI membrane under different alkali treatment times is shown.

[0030] Figure 8 The porosity of the original PI membrane and the PI membrane under different alkali treatment times is shown.

[0031] Figure 9 The gel content of the original PI membrane and PI membranes treated with different alkali times;

[0032] Figure 10 The surface water contact angle of the original PI membrane and PI membranes treated for different alkali times;

[0033] Figure 11 The pervaporation performance of the original PI membrane and PI membranes with different alkali treatment times;

[0034] Figure 12 The pervaporation performance of modified PI membranes under different NaOH concentrations;

[0035] Figure 13 Infrared spectra of the original PI film and PI films crosslinked with different metal ions;

[0036] Figure 14 SEM morphology of cross-sections of PI films with different metal ions;

[0037] Figure 15 The gel content of the original PI membrane and PI membranes crosslinked with different metal ions;

[0038] Figure 16 The pervaporation properties of the original PI membrane and PI membranes crosslinked with different metal ions are compared. Detailed Implementation

[0039] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention. Furthermore, the technical features involved in the various embodiments of this invention described below can be combined with each other as long as they do not conflict with each other.

[0040] See Figure 1 The modification process of the dense polymer membrane of this invention includes: first, providing a raw dense polymer membrane; then, contacting its lower side with an etchable alkaline solution; and simultaneously modifying it by etching and metal (metal contained in the alkaline solution) crosslinking in a green and gentle manner from the lower side to the upper side, to obtain an alkali-modified membrane; and finally, obtaining a metal-crosslinked membrane through a metal salt solution. Using the method of this invention, the thickness of the membrane selective layer and the pore size of the support layer can be controlled simultaneously, as well as the degree of crosslinking and hydrophilicity can be improved. While maintaining the membrane separation performance, its flux is significantly increased, and its performance remains stable during long-term separation.

[0041] In this invention, the polyimide film, polyacrylonitrile film, or polyvinylidene fluoride film used can be a self-prepared film or a commercially available film.

[0042] Example 1

[0043] Example 1 includes the following three steps:

[0044] 1. Preparation of the original PI membrane

[0045] Commercial polyimide Torlon powder was first dried in a vacuum drying oven at 50 °C for 12 h, then dissolved in the highly polar organic solvent N-methylpyrrolidone (NMP) to prepare a casting solution with a composition of 15 / 85 (w / w) Torlon / NMP. The solution was mechanically stirred at 40 °C for 48 h to ensure complete dissolution of Torlon in NMP. The prepared casting solution was then allowed to stand at room temperature for at least 12 h until all air bubbles were completely removed. For the casting process, a glass plate was first wiped clean with ethanol to ensure it was free of scratches. After the ethanol had completely evaporated, an appropriate amount of casting solution was poured onto the glass plate. Then, a 250 μm thick doctor blade was used to evenly spread the casting solution onto the glass plate. The glass plate was then carefully placed on a graphite heating stage at 70 °C to remove NMP from the casting solution. After heating for 12 h, the glass plate was transferred to a 50 °C water bath to allow the PI film to detach from the glass plate on its own. The prepared original PI membrane was retrieved, freeze-dried for 12 h, and then stored at room temperature under dry conditions for subsequent experiments.

[0046] 2. Preparation of alkali-modified PI film

[0047] The prepared polyimide (PI) membranes were cut to appropriate sizes and fixed in a plate frame. Then, NaOH solutions of different concentrations (0.1–10 M) were poured onto the surface of the fixed membrane, immersing the underside of the PI membrane in the alkaline solution for different times (0.5–10 h). After removing the membrane, the surface of the PI membrane was washed with distilled water at least three times to remove residual NaOH solution. The prepared alkali-modified PI membranes were freeze-dried for 12 h and then stored at room temperature under dry conditions for subsequent experiments.

[0048] 3. Preparation of metal ion crosslinked PI membrane

[0049] First, the alkali-modified PI membrane was fixed in a plate frame. Then, 0.01 M solutions of CaCl2 aqueous solution, CuCl2 aqueous solution, and FeCl3 ethanol solution (the FeCl3 ethanol solution was used to avoid damage to the alkali-modified PI membrane due to the strong acidity of the FeCl3 aqueous solution) were poured in for ion exchange for 2 h. Afterward, the membrane was removed and rinsed with deionized water at least three times to completely remove any residual salt solution from the membrane surface. The prepared metal ion crosslinked PI membrane was freeze-dried for 12 h and then stored at room temperature under dry conditions for subsequent experiments.

[0050] Pervaporation performance test:

[0051] First, cut the membrane sample to be tested into a suitable size and fix it on a surface such as... Figure 2 The bottom of the membrane tank in the pervaporation device shown (effective area is 13.5 cm²) 2 Add approximately 200 mL of feed solution, with a composition of 90 / 10 (w / w) ethanol / water. To reduce concentration polarization during the test, the stirrer should be turned on and the stirring speed set to 400 rpm. After turning on the heating device and setting the temperature to 60 °C, turn on the vacuum pump to ensure that the pressure under the membrane remains below 3 mbar throughout the test. Before collecting the first sample, maintain the system under the above conditions for at least 2 hours until the system stabilizes. After the system stabilizes, place the receiving bottle in a cold trap filled with liquid nitrogen to collect the permeate. Samples should be collected at least 4 times, and then the composition of the permeate sample should be measured using gas chromatography.

[0052] The performance parameters of membrane pervaporation can be expressed as flux J (g / m³). 2 h) and separation factor α are used to characterize the relationship, which can be calculated by formula (1) and formula (2) respectively.

[0053] (1)

[0054] (2)

[0055] In the above formula, m represents the mass of the permeate (g), and A represents the effective membrane area (m²).2 ), t represents the test time (h), and y and x represent the mass fraction of a certain component in the permeate and feed liquid, respectively.

[0056] Example 2: Preparation and characterization of metal ion crosslinked PI film

[0057] The reaction mechanism of alkali treatment and metal ion crosslinking of PI membrane is as follows: Figure 3 As shown. After the PI casting solution is coated to form a film, the PI film support layer is dip-coated with NaOH solution on one side to obtain an alkali-modified PI film (i.e., a sodium ion crosslinking film). + -PI), and then ion exchange with salt solutions containing different metal ions to prepare cross-linked PI membranes (M) with different metal ions. n+ -PI). PI membranes in alkaline solutions due to OH... - The attack on the imide groups on the PI chain segments causes the CN bonds of the PI segments to break, leading to ring-opening and the formation of polymers containing carboxylate groups. Furthermore, stable coordination bonds can be formed subsequently through complexation between carboxylate ions and metal ions. Based on this, this invention simultaneously modifies an integrated PI film through simple alkali treatment and metal crosslinking. The present invention uses the FTIR and X-ray photoelectron spectroscopy (XPS) spectra of the original PI film and the modified PI film treated with 0.1 M NaOH for 2 h as examples. Figure 4 Table 1 clarifies the reaction mechanism.

[0058] Table 1. Surface elemental composition of the original and modified PI films (obtained from X-ray photoelectron spectroscopy (XPS) spectra)

[0059]

[0060] Example 3 Effect of different alkali treatment times

[0061] When PI membranes are treated with NaOH solution, the hydroxide ions (OH-) - Attacking the imide groups on the PI chain segments disrupts the PI chain structure, causing irreversible damage to the chemical composition and microstructure of the PI film, and directly affecting its performance. To investigate the effect of alkali treatment time on alkali-modified PI films, alkali-modified PI films were prepared using 0.1 M NaOH solution with alkali treatment times of 0.5 h, 1 h, 2 h, 5 h, and 10 h. FTIR spectroscopy confirmed the changes in the chemical structure of the modified PI films. Figure 5 The X-ray photoelectron spectroscopy (XPS) characterization results (Table 2) show the changes in element types and relative contents of the original PI film and the PI film modified with alkali at different times. With increasing alkali treatment time, the Na content in the modified PI film gradually increases. This indicates that the degree of etching of the PI film by NaOH increases with increasing alkali treatment time.

[0062] Table 2. Surface elemental composition of PI films at the original and different alkali treatment times

[0063]

[0064] To more intuitively reflect the etching degree of the PI film under different alkali treatment times, the weight loss rate of the PI film at different alkali treatment times was characterized. For example... Figure 6 As shown, the degree of etching of the PI film gradually increases with the increase of alkali treatment time. It was also observed that the weight loss rate was slow before the alkali treatment time reached 1 hour, while the weight loss rate increased significantly after the alkali treatment time exceeded 1 hour.

[0065] Similar conclusions can be drawn from characterizing the cross-sectional microstructure of the PI film using scanning electron microscopy (SEM), such as... Figure 7 As shown, the untreated original PI membrane has a uniform and dense cross-section. After alkali treatment, a porous structure appears on one side of the PI membrane. With the extension of alkali treatment time, the depth and number of pores in the porous structure continuously increase, while the thickness of the dense layer continuously decreases. When the alkali treatment time is 0.5 h, only a small number of sparsely distributed porous structures appear on one side of the PI membrane, and the pore depth is relatively shallow, only distributed on the surface. When the alkali treatment time is increased to 2 h, the distribution density of the porous structure is significantly improved, and the pore depth increases to about 1 / 3 of the membrane thickness. When the alkali treatment time reaches 5 h, a completely loose porous structure can be observed on one side of the PI membrane, and the pore depth further increases to 1 / 2 of the membrane thickness. When the alkali treatment time reaches 10 h, the overall cross-sectional morphology of the PI membrane is loose and porous, with only a small number of dense layers remaining.

[0066] To further understand the changes in the pore structure of alkali-modified PI membranes, the porosity of the original PI membrane and PI membranes treated with different alkali times was tested. Figure 8 As shown, the porosity of the PI film gradually increases with increasing alkaline treatment time. When the alkaline treatment time reaches 2 hours, the porosity increases to a certain extent. Further extending the alkaline treatment time to 5 hours reveals a significant increase in PI film porosity. This further demonstrates that alkaline etching affects the morphology of the PI film. Alkaline etching modifies the originally dense and uniform PI film into an alkaline-modified PI film with a loose support layer and a dense selective layer. Furthermore, the thickness of the selective and support layers can be controlled by varying the alkaline treatment conditions.

[0067] Alkali treatment not only etches the membrane, but the Na ions in the NaOH solution also crosslink the formed polyimide molecular chains. Subsequent ion exchange further enhances the strength of the metal complex crosslinking. The crosslinking strength can be characterized by the mass retention rate (gel content) of the PI membrane in the highly polar organic solvent N-methylpyrrolidone (NMP). Figure 9 It can be seen that the degree of crosslinking of the PI film gradually increases with the increase of alkali treatment time. During the experiment, it was found that the original PI film completely dissolved after 10 min in NMP. When the alkali treatment time was ≤1 h, the alkali-modified PI film basically did not undergo crosslinking. The PI film treated with alkali for 0.5 h completely dissolved after 24 h. The PI film treated with alkali for 1 h only had a small amount of transparent flocculent residue after immersion in NMP for 48 h. When the alkali treatment time was increased to 2 h, a certain amount of transparent flocculent solids could still be observed after 48 h. When the alkali treatment time reached 5 h and 10 h, a small amount of transparent film fragments could be observed in NMP after 48 h. The experimental results indicate that alkali treatment not only etches the PI film, but also the Na+ in the alkali solution... + It can also crosslink PI films, and when the crosslinking reaches a certain degree, it can significantly improve their solvent resistance.

[0068] Alkali modification not only increases the porosity and crosslinking degree of polyimide membranes, but also transforms the imide functional groups in the polymer membrane into imide acid functional groups. Combined with the introduction of metal ions, this leads to an improvement in the membrane's hydrophilicity. The water contact angle at the membrane surface (…) Figure 10 The results show that as the alkali treatment time increases, the water contact angle on the PI membrane surface gradually decreases, indicating that the hydrophilicity of the PI membrane gradually increases.

[0069] Therefore, the PI membrane modified with alkali exhibits significantly improved pervaporation performance due to increased porosity, enhanced crosslinking degree, and improved surface hydrophilicity. Figure 11 As can be seen, when the alkali treatment time does not exceed 5 hours, the flux and separation factor of the modified membrane are both higher than those of the unmodified membrane. Firstly, the increase in flux can be attributed to the simultaneous improvement in membrane microstructure and hydrophilicity: alkali modification introduces a porous structure into the dense original PI membrane, thinning the selective layer and thus increasing membrane flux; simultaneously, the introduction of alkali modification, polyimide acid, and metal ions enhances the membrane's hydrophilicity. For pervaporation dehydration membranes, increased membrane hydrophilicity leads to an increase in the separation factor. This increase in the separation factor can be attributed to the improved crosslinking degree and hydrophilicity. The crosslinking of the alkali-modified PI membrane with the metal coordinating ions introduced by subsequent ion replacement enhances the membrane's resistance to swelling, resulting in more stable pervaporation performance and the maintenance of high separation selectivity during testing.

[0070] Example 4 Effect of different alkali treatment concentrations

[0071] To investigate the effect of alkali treatment concentration on PI membranes, NaOH solutions with concentrations of 0.1 M, 1 M, 2 M, 5 M, and 10 M were prepared, and alkali-modified PI membranes with different alkali treatment times were fabricated at the corresponding concentrations. When the alkali treatment time was set to 1 h, with the increase of NaOH concentration, the color of the PI membrane gradually lightened, the transparency gradually increased, and slight wrinkles appeared on the membrane surface. The pervaporation performance of this group of alkali-modified PI membranes was then tested. Figure 12 As shown, compared with the original PI membrane, the flux and separation factor of the alkali-modified PI membrane were improved to a certain extent. With increasing NaOH concentration, the flux gradually increased while the separation factor gradually decreased. When the alkali treatment concentration exceeded 5 M, the membrane flux increased significantly, and the separation factor decreased significantly. Combined with the changes in membrane appearance observed in the experiment, this indicates that NaOH disrupts the relatively rigid and dense structure of the PI membrane during alkali treatment, thereby increasing the flux. Furthermore, a small amount of Na+ ions were present on the membrane surface after alkali treatment. + Crosslinking on the PI membrane enhances its hydrophilicity and increases the separation factor.

[0072] Example 5: Effects of different metal crosslinking types

[0073] The effects of alkaline treatment conditions on PI membranes were discussed above, and the optimal alkaline treatment condition was determined to be treatment with 0.1M NaOH for 2 h. The preceding experimental results demonstrate that under these conditions, Na… + While PI membranes can undergo some crosslinking, the degree of crosslinking is very low. Therefore, metal ion replacement is considered to further optimize the PI membrane. This invention selects Ca... 2+ Cu 2+ and Fe 3+ The alkali-modified PI membrane was optimized.

[0074] See Figure 13 The chemical structures of the original PI film and PI films crosslinked with different metal ions were characterized using FTIR. Compared to alkali-modified PI films (Na ion crosslinking), those crosslinked with Ca... 2+ Cu 2+ and Fe 3+ After metal ion replacement, the characteristic peaks of the amide group shifted more significantly, while the peak intensities of the carboxylate characteristic peaks also increased. This indicates that the degree of crosslinking of the PI film was improved after metal ion replacement.

[0075] To observe the changes in the microstructure of PI films after metal ion exchange, SEM was used to characterize the cross-sectional microstructure of PI films cross-linked with different metal ions. Figure 14It can be observed that although metal ions crosslink the PI membrane, the membrane structure differs from that after conventional chemical crosslinking. The support layer of the PI membrane does not become denser after metal ion crosslinking and still retains a porous structure. This indicates that metal ion exchange can more effectively crosslink the PI membrane without damaging its microstructure, maintaining the high flux resulting from alkali modification while improving the separation performance of the PI membrane.

[0076] To more intuitively display the degree of crosslinking of PI membranes, the gel content of the original PI membrane and PI membranes crosslinked with different metal ions was tested, such as... Figure 15 As shown, the degree of crosslinking of the PI film increased significantly after metal ion replacement. The gel content of the alkali-modified PI film was only 4.65%, while that of Cu... 2+ and Ca 2+ The gel content of the cross-linked PI films all reached over 50%, an increase of more than 10 times, indicating that different metals have different complexing abilities, resulting in different complexing strengths of the cross-linked polyimide films. Their stability follows the principle of Fe... 3+ -PI ≈ Cu 2+ -PI > Ca 2+ -PI > Na + - The order of PI > unmodified PI.

[0077] The pervaporation performance test results of the original PI membrane and the metal ion crosslinked PI membrane are as follows: Figure 16 Comparing alkali-modified PI membranes and metal ion-replaced PI membranes, the latter showed a slight decrease in flux but a significant increase in separation factor. This is attributed to the increased crosslinking degree of the PI membrane after metal ion replacement. The performance differences of PI membranes crosslinked with different metal ions mainly stem from the varying binding abilities of different metal ions to the amide functional groups in the PI membrane. Overall, compared to alkali-modified PI membranes, Cu... 2+ Cross-linked PI membranes have the best performance, increasing the separation factor to three times the original value while sacrificing a small amount of flux, resulting in a significant improvement in separation performance.

Claims

1. A method for preparing an asymmetric dense polymer pervaporation membrane, characterized in that, The method comprises the following steps: 1) contacting the lower side of the integrated symmetric dense polymer membrane with an alkali solution for a period of time, followed by washing and drying; 2) ion exchange treatment of the membrane treated in step 1) with a metal salt solution, followed by washing and drying.

2. A method of making an asymmetric, dense polymeric pervaporation membrane as claimed in claim 1, characterized by: The alkali solution is an aqueous solution of sodium hydroxide, potassium hydroxide, calcium hydroxide, or barium hydroxide, with a concentration of 0.1-10 M; the period of time is 0.5-12 h.

3. A method of making an asymmetric, dense polymeric pervaporation membrane as claimed in claim 2, characterized in that: The concentration of the alkali solution is 0.1-2 M; the period of time is 0.5-10 h.

4. The method of making an asymmetric, dense polymer pervaporation membrane according to claim 1, wherein: The metal ion in the metal salt solution is Ca 2+ , Ni 2+ , Zn 2+ , Mg 2+ , Co 2+ , Ag + , Fe 2+ , Al 3+ , Cu 2+ or Fe 3+ ; the concentration of the metal salt solution is 0.01-1 M; the ion exchange treatment time is 1-24 h.

5. The method of making an asymmetric, dense polymer pervaporation membrane according to claim 1, wherein: The integrated symmetric dense polymer membrane is a polyimide membrane, a polyacrylonitrile membrane, or a polyvinylidene fluoride membrane.

6. An asymmetric dense polymer pervaporation membrane characterized in that, Prepared by the method of any one of claims 1-5.

7. An asymmetric dense polymeric pervaporation membrane as claimed in claim 6, wherein: The asymmetric dense polymer pervaporation membrane has a cross-sectional morphology of asymmetric structure, comprising a dense layer and a support layer with a pore structure; and the gel content of the membrane in a strong organic solvent is not less than 50 wt%.

8. Use of the asymmetric dense polymer pervaporation membrane of claim 6 or 7 in a pervaporation separation process.

9. Use according to claim 8, wherein: The pervaporation separation process is used to separate water from an organic substance aqueous solution with a mass concentration of not less than 50%.